2016
DOI: 10.1007/s10071-016-0978-1
|View full text |Cite|
|
Sign up to set email alerts
|

Acoustic behavior associated with cooperative task success in bottlenose dolphins (Tursiops truncatus)

Abstract: Although many species have proven capable of cooperating to achieve common goals, the role of communication in cooperation has received relatively little attention. Analysis of communication between partners is vital in determining whether actions are truly cooperative rather than serendipitous or learned via trial and error (Chalmeau and Gallo in Behav Process 35:101-111, 1996a. doi: 10.1016/0376-6357(95)00049-6 , Primates 37:39-47, 1996b. doi: 10.1007/BF02382918 ). Wild cetaceans often produce sounds during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 73 publications
0
16
0
2
Order By: Relevance
“…This result also reveals that chirps and whistles should be studied separately (Gridley et al, ). While an increase in whistle rates during social play could be expected, the increase during solitary play was more surprising, as most studies consider whistles primarily as social signals (Caldwell et al, ; dos Santos, Louro, Couchinho, & Brito, ; Eskelinen et al, ; Gridley et al, ; Herzing, ; Janik & Slater, ; King & Janik, ; Kuczaj II, Eskelinen, Jones, & Borger‐Turner, ). However, a few studies have found that whistles could be produced in more nonsocial contexts, such as feeding (Acevedo‐Gutiérrez & Stienessen, ; dos Santos et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result also reveals that chirps and whistles should be studied separately (Gridley et al, ). While an increase in whistle rates during social play could be expected, the increase during solitary play was more surprising, as most studies consider whistles primarily as social signals (Caldwell et al, ; dos Santos, Louro, Couchinho, & Brito, ; Eskelinen et al, ; Gridley et al, ; Herzing, ; Janik & Slater, ; King & Janik, ; Kuczaj II, Eskelinen, Jones, & Borger‐Turner, ). However, a few studies have found that whistles could be produced in more nonsocial contexts, such as feeding (Acevedo‐Gutiérrez & Stienessen, ; dos Santos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In captivity, positively reinforced dolphins produce chirps more frequently than non‐reinforced individuals (Caldwell, Caldwell, & Tyack, ). Pulsed sounds are traditionally associated with echolocation clicks (Au, ), but they can be observed during foraging (Eskelinen, Winship, Jones, Ames, & Kuczaj, ), and sometimes in agonistic interactions (Vollmer, Hayek, Heithaus, & Connor, ). This category, less explored than whistles, could include several functional sub‐categories (Gridley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Основная функция разговорного языка -передача и обмен информацией между животными. Можно полагать, что именно наличие разговорного языка позволяет дельфинам организовывать различные виды сотрудничества и кооперации во время поиска и ловли рыбы [3,7,19]. Это свидетельствует, в свою очередь, о наличии у них сложных видов психической и интеллектуальной деятельности.…”
Section: результаты и обсуждениеunclassified
“…Вместе с тем совершенная эхолокационная Морской биологический журнал 2018 Том 3 № 2 система животных позволяет обнаруживать объекты питания (рыбные скопления) на расстоянии до 13 км и классифицировать их за сотни метров, чтобы двигаться к ним кратчайшим путём. Более того, дельфины могут оптимизировать пищевое поведение для экономии энергии, организуя различные виды сотрудничества и сложной кооперации между собой во время поиска и ловли рыбы [3,7,19].…”
Section: результаты и обсуждениеunclassified
“…Recent studies have examined dolphin cooperation (Eskelinen, Winship, Jones, Ames, & Kuczaj, 2016; Jaakkola, Guarino, Donegan, & King, 2018; Kuczaj, Winship, & Eskelinen, 2015). Kuczaj et al, (2015) introduced an apparatus to a group of six dolphins under human care that contained fish and ice reinforcement and was designed to be manipulated by pairs of dolphins.…”
Section: Introductionmentioning
confidence: 99%